2021
DOI: 10.3389/fmars.2021.710124
|View full text |Cite
|
Sign up to set email alerts
|

Aquaculture Impacts on China’s Marine Wild Fisheries Over the Past 30 Years

Abstract: China is the world’s largest producer of aquaculture and capture fisheries. How this country develops its aquaculture sector and whether such development can relieve pressure on wild fisheries remain a contentious issue in the past and for the future. This study aims to provide a broad assessment on the impact of aquaculture development in different periods on marine wild fisheries on the basis of aquaculture and marine wild fish catch data from all the coastal provinces of China. China’s aquaculture and captu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 31 publications
0
11
0
Order By: Relevance
“…biodiversity conservation, climate change, fisheries management, fishing pressure, functional diversity, marine fish Here, we used the reported marine fish catch data of China for the past three decades and a comprehensive set of functional traits for the reported species to explore how the FD of commercial marine fish communities responds to climate change and changes in fishing pressure. With the rapid economic growth and huge population increase in China over the past decades and the associated diversification of fish consumption and increasing demand (Zhao et al, 2019(Zhao et al, , 2021, not only do consumers exhibit a clear preference for predatory and large species, but there is also an incentive for the overexploitation of small species resources, such as forage species (e.g., anchovy), to meet the large demand for fishmeal (Cao et al, 2015;Chiu et al, 2013). Although China has taken a series of measures to reduce its dependence on marine wild fishery resources, which have started to exhibit positive effects (Zhao et al, 2021), China's marine fishing practices in the past decades have been exhaustive and largely non-selective, with minimal discard because a market exists for a wider range of species and sizes than those that are typically saleable in other locales (Costello, 2017;Costello et al, 2016;Szuwalski et al, 2017;Zhang et al, 2020;Zhao et al, 2021).…”
Section: Main Conclusionmentioning
confidence: 99%
See 1 more Smart Citation
“…biodiversity conservation, climate change, fisheries management, fishing pressure, functional diversity, marine fish Here, we used the reported marine fish catch data of China for the past three decades and a comprehensive set of functional traits for the reported species to explore how the FD of commercial marine fish communities responds to climate change and changes in fishing pressure. With the rapid economic growth and huge population increase in China over the past decades and the associated diversification of fish consumption and increasing demand (Zhao et al, 2019(Zhao et al, , 2021, not only do consumers exhibit a clear preference for predatory and large species, but there is also an incentive for the overexploitation of small species resources, such as forage species (e.g., anchovy), to meet the large demand for fishmeal (Cao et al, 2015;Chiu et al, 2013). Although China has taken a series of measures to reduce its dependence on marine wild fishery resources, which have started to exhibit positive effects (Zhao et al, 2021), China's marine fishing practices in the past decades have been exhaustive and largely non-selective, with minimal discard because a market exists for a wider range of species and sizes than those that are typically saleable in other locales (Costello, 2017;Costello et al, 2016;Szuwalski et al, 2017;Zhang et al, 2020;Zhao et al, 2021).…”
Section: Main Conclusionmentioning
confidence: 99%
“…With the rapid economic growth and huge population increase in China over the past decades and the associated diversification of fish consumption and increasing demand (Zhao et al, 2019(Zhao et al, , 2021, not only do consumers exhibit a clear preference for predatory and large species, but there is also an incentive for the overexploitation of small species resources, such as forage species (e.g., anchovy), to meet the large demand for fishmeal (Cao et al, 2015;Chiu et al, 2013). Although China has taken a series of measures to reduce its dependence on marine wild fishery resources, which have started to exhibit positive effects (Zhao et al, 2021), China's marine fishing practices in the past decades have been exhaustive and largely non-selective, with minimal discard because a market exists for a wider range of species and sizes than those that are typically saleable in other locales (Costello, 2017;Costello et al, 2016;Szuwalski et al, 2017;Zhang et al, 2020;Zhao et al, 2021). Moreover, the relative marine fishing capacity and effort have remained basically constant over the past 30 years across all seas (Supporting Information Figures S1-S3).…”
Section: Main Conclusionmentioning
confidence: 99%
“…In recent years, Chinese government has invested extensive efforts into curbing overfishing and developing sustainable fisheries, and prioritized fishery resource conservation in marine fishery management (Han et al, 2018;Su et al, 2020;Zhao et al, 2021). Zhao et al, 2021 indicated that China's aquaculture is transforming into a sustainable development pattern with low input and high output, reducing its dependence on marine wild fishery resources.…”
mentioning
confidence: 99%
“…In recent years, Chinese government has invested extensive efforts into curbing overfishing and developing sustainable fisheries, and prioritized fishery resource conservation in marine fishery management (Han et al, 2018;Su et al, 2020;Zhao et al, 2021). Zhao et al, 2021 indicated that China's aquaculture is transforming into a sustainable development pattern with low input and high output, reducing its dependence on marine wild fishery resources. Along with the development of Chinese sustainable capture fisheries and increasing climate change in recent decades, an enhanced understanding of how biodiversity changes in space and time could improve decision-making about establishing protected areas, sustainable fishery management, etc.…”
mentioning
confidence: 99%
See 1 more Smart Citation